2010
DOI: 10.1152/ajpregu.00348.2010
|View full text |Cite
|
Sign up to set email alerts
|

Muscle protein synthesis and gene expression during recovery from aerobic exercise in the fasted and fed states

Abstract: Harber MP, Konopka AR, Jemiolo B, Trappe SW, Trappe TA, Reidy PT. Muscle protein synthesis and gene expression during recovery from aerobic exercise in the fasted and fed states. Am J Physiol Regul Integr Comp Physiol 299: R1254 -R1262, 2010. First published August 18, 2010 doi:10.1152/ajpregu.00348.2010.-The purpose of this investigation was to assess mixed-muscle fractional synthesis rate (FSR) and the expression of genes involved in skeletal muscle remodeling after aerobic exercise in the fasted and fed s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
66
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 93 publications
(71 citation statements)
references
References 56 publications
5
66
0
Order By: Relevance
“…Importantly, cell swelling has been shown to trigger protein synthesis through the activation of mTOR and mitogen-activated protein kinase (MAPK) 40) . Previous studies confirmed that a bout of continuous cycling (30-60 min at 40-75% V ・ O2max) was effective in temporarily increasing thigh thickness (swelling) (unpublished data), activating both the mTOR 43) and MAPK 44) signaling pathways, and increasing muscle protein synthesis 45) . Hence the contribution of intracellular fluid pressure and cellular swelling may explain muscle hypertrophy that results from cycle exercise.…”
Section: Muscle Hypertrophy With Endurance Trainingmentioning
confidence: 62%
See 1 more Smart Citation
“…Importantly, cell swelling has been shown to trigger protein synthesis through the activation of mTOR and mitogen-activated protein kinase (MAPK) 40) . Previous studies confirmed that a bout of continuous cycling (30-60 min at 40-75% V ・ O2max) was effective in temporarily increasing thigh thickness (swelling) (unpublished data), activating both the mTOR 43) and MAPK 44) signaling pathways, and increasing muscle protein synthesis 45) . Hence the contribution of intracellular fluid pressure and cellular swelling may explain muscle hypertrophy that results from cycle exercise.…”
Section: Muscle Hypertrophy With Endurance Trainingmentioning
confidence: 62%
“…A study by Harber et al (2010) showed that Forkhead transcription factor 3A (FOXO3A), which is an indicator of proteolytic systems, significantly decreased 6 h after an acute bout of 60 min cycle exercise compared to rest 45) . Furthermore, 12 weeks of cycle training, which induced muscle hypertrophy, significantly lowered the resting level of mRNA expression of FOXO3A 47,48) .…”
Section: Muscle Hypertrophy With Endurance Trainingmentioning
confidence: 99%
“…Konopka et al (27,44) have shown that 12-week cycle training induced muscle hypertrophy and significantly reduced mRNA expression of Forkhead transcription factor 3A (FOXO3A) at rest with a trend for its downstream targets, Atrogin-1 and MuRF1, to also be reduced. Furthermore, FOXO3A significantly decreased 6 hours after an acute bout of 60-minute cycle exercise compared to rest (28). Therefore, following a bout of cycle exercise, the reduction of proteolytic mRNA expression may be another factor contributing to muscle hypertrophy.…”
Section: Proteolytic Gene Expressionmentioning
confidence: 94%
“…Several mitogen-activated protein kinase (MAPK) signaling pathways such as extracellular signal-regulated kinase (ERK) and p38-MAPK signaling pathways also play an important role in muscle protein synthesis (16,53). Some studies have shown that a bout of cycle exercise activated both mTOR (55) and MAPK (87) signaling pathway as well as muscle protein synthesis (28). However, the magnitude of increase appears to be smaller for cycle exercise compared to resistance exercise.…”
Section: Muscular Adaptations To Cycle Trainingmentioning
confidence: 99%
See 1 more Smart Citation